Factors influencing the assimilation of cloud computing services and its effect on operational effectiveness in the Malaysian public sector. - Hasimi Sallehudin (2017)
The research on IT innovation, particularly cloud computing services are still at the early stage. The reason t o explain the cloud computing assimilation as well as the understanding of the operational performance still remains unclear. To investigate this issue, this study has examined the assimilation of cloud computing by measuring the organization ’s initiatio n and implementation of cloud computing services and resources in the Malaysian public sector. Grounded by the Diffusion of Innovation Theory (DOI), Technology Organization Environment Framework (TOE) and IS Success Model, this study proposes a framework b y decomposing Technological characteristic, Organizational characteristics, Environmental characteristics and Human characteristics as factors. A total of 169 agencies from the Malaysian public sector have participated in this study. Data for all the study variables have been collected through self administered survey questionnaires. Structural Equation Modelling (SEM) is the main statistical technique used in this study. The study has shown that the effect of the operational effectiveness of cloud computin g implementation is at the lower level. The study also reveals that only factors of technological, organizational and human characteristics are found to have significant effect on cloud computing implementation. Whereas, environmental factors insignificant ly influence the implementation of cloud computing. With regard to antecedents’ effect on the initiations, there are only three factors which are found to be significant, namely technological, environmental and human characteristics. Whereas, organizationa l factors insignificantly influence the initiation of cloud computing. Overall, the results indicate that the model provides a good understanding of the factors that influence the initiation to implement and the actual implementation of cloud computing ser vices and resources as well as operational performance. As predicted, decomposition of the initiation to implement provides more specific mediated factors that influence the actual implementation. Based on the findings, the theoretical and practical implic ations of the study as well as limitations and suggestions for future studies are also discussed.